Possible mechanisms of treatment for spinal cord injury repair with tanshinone IIA - Jia, Zhiwei; Wen, Tianlin; Zhang, Yuning (Frontiers in Molecular Neuroscience, 2023)
Tanshinone IIA serves as a coenzyme for certain biochemical reactions, exhibiting various pharmacological effects in the treatment of neurological diseases including spinal cord injury (SCI), however, its working mechanism in the treatment of SCI is not clear. Based on previous research, we believe that tanshinone IIA promotes the survival and repair of nerves after spinal cord injury through its pharmacological effects such as anti-inflammatory, antioxidant, and prevention of cellular apoptosis in the spinal cord.